Attempts to reduce biodiesel blends NOX pollutant emissions by ultrasonic conditioning - Mariasiu, Florin (Transport, 2014)
The conditions imposed by the renewable energy Directive 2009/28/EC make it mandatory for EU member countries to ensure that by 2020 fossil fuels used in the transport sector contain a 10% component of biofuel. The 10% limit is based on results of experiments conducted by engine manufacturers and researchers in the biofuels domain, which show that this percentage can be used in IC engines without major technical changes to equipment and engine systems. Taking into account that increasing the percentage of biodiesel in blends results in significant reductions of CO2 emissions, an immediate way to surpass the 10% limit is to carry out external and/or internal processes that will act on the physico-chemical properties of those biofuels. This paper presents data and results from experiments examining the process of ultrasonic irradiation of rapeseed oil methyl ester type biodiesel. The results show the effects of the irradiation process on biodiesel physical parameters such as density, kinematic viscosity, speed of sound through the medium, and isentropic bulk modulus. The values of these parameters directly influence the operation, performance and pollutant emissions of diesel engines. Primary results obtained demonstrate the possibilities of using what we call here the B25 blend with low-cost procedures and without major technical intervention in the equipment used to construct diesel engines. Two parameters important for the injection process (kinematic viscosity and density) show equal values for B25Us_irr ultrasonically irradiated for 350 seconds and diesel fuel ultrasonically irradiated for 420 seconds. The range of the achieved NOx pollutant emission reduction was between 18.2% for the ultrasonically irradiated blend B25Us_irr (no load) and 1.4% for the ultrasonically irradiated blend B100Us_irr (100% load), when compared with untreated basic biodiesel.First Published Online: 25 Mar 2014